Antepartum Monitoring of the Fetus Chronically Exposed to Opioids: What To Expect and Why Do We Intervene? [22C]. (May 2018) - Brar, Bobby; Hom, Katherine; Nat, Manita; Lua, Lannah L.; Iriye, Brian; Jackson, David
Abstract : INTRODUCTION: Chronic opioid dependence for maternal pain management, methadone maintenance, or suboxone therapy is an increasing phenomenon in obstetrics. Opioids may depress fetal neurobehavioral status and may change reactivity or variability of fetal heart rate patterns. Our primary objective was to determine which fetal assessment modality best identifies the vulnerable opioid exposed fetus. METHODS: A retrospective review from January 2016 through April 2017 at two MFM antenatal centers identified singleton, non-syndromic fetuses with daily opioid exposure. Non-stress tests (NST), biophysical profiles (BPP), amniotic fluid index (AFI), umbilical artery Doppler's (UAD), and serial biometry were reanalyzed. Test characteristics and frequency of interventions for abnormal monitoring were quantified. RESULTS: Criteria was met in 27 patients (77.8% methadone (n=21), 14.8% prescription opioid (n=4) and 7.4% suboxone (n=2)). There were 112 growth scans, 102 BPP, 112 NST, and 81 UAD measurements. Time to NST first acceleration was <20 minutes in 92.5%. Abnormal testing causing delivery occurred in 6/27 patients (22.2%), all at 36-38 weeks. Isolated oligohydramnios was 2/27 (7.4%, occurring at 37 and 38 weeks), oligohydramnios with IUGR 2/27 (7.4%, both at 36 weeks), nonreactive NST 1/27 (3.7%, 38 weeks), and BPP 6/10 1/27 (3.7%, 36 weeks). UAD did not change management. Earliest IUGR was seen at 32 weeks. CONCLUSION: Antenatal testing of the singleton, chronic opioid exposed fetus should include third trimester serial growth ultrasounds and BPP or NST-AFI scheduled no later than 34-35 weeks. Continuing study on a larger cohort is needed to define optimal monitoring based upon category of opioid dependence.